Review of tribological behavior of graphene coatings on piston rings in engines. Issue 2 (21st January 2019) - Acunaş Karagöz, Zeynep Burcu; Demirtaş, Selman; Kaleli, Hakan; Yüksek, Levent; Çıtak, Emre
Abstract : Purpose: This study aims to find out friction and wear characteristics of graphene and graphene coating deposited by the Chemical Vapor Deposition (CVD) process on Honda GX270 engine (nodular cast iron) piston rings experimentally investigated under boundary lubricated conditions. Design/methodology/approach: This study consists of two stages: tribotest and engine tests. First test was conducted through a reciprocating tribotest machine and second test was conducted through an engine bench with a duration of 75h. Engine piston ring was coated with graphene by two different methods: transfer method and direct CVD method. Findings: Graphene has been demonstrated to be a potential and promising candidate for wear- and scratch-resistant coating because it is the thinnest, lightest and strongest known nanomaterial. In this case, the ability of a mono-layer graphene film to withstand high pressure differences (6 atm) indicates its mechanical robustness. It can effectively prevent or reduce mechanical failure by strengthening and toughening the loaded surface as well as by transferring the stress throughout the structure. The positive tribological outcomes of the graphene reinforced material under various dynamic loads revealed the potential of graphene-based coatings in macro - and micro-tribology. Originality/value: This study fulfils an identified need to study for automotive industry a coating which is wear and scratch resistant.